Transportation, logistics, and supply chain management in home healthcare - Euchi, Jalel, 1980- (Advances in logistics, operations, and management science (ALOMS) book series., 2020)
With advancing technology and the digitization of the modern era, businesses are required to adopt the latest innovations computer science and information technology have to offer. The field of home healthcare must utilize the finest available operations management systems in order to remain relevant in a globalized world while also providing the best treatment possible to its patients. Transportation, Logistics, and Supply Chain Management in Home Healthcare: Emerging Research and Opportunities is an essential reference source that provides theoretical and empirical research on logistics mana.